Energetic and exergetic performance evaluations of a geothermal power plant based integrated system for hydrogen production - Yuksel, Yunus Emre; Ozturk, Murat; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
In this paper, we propose an integrated system aiming for hydrogen production with by-products using geothermal power as a renewable energy source. In analyzing the system, an extensive thermodynamic model of the proposed system is developed and presented accordingly. In addition, the energetic and exergetic efficiencies and exergy destruction rates for the whole system and its parts are defined. Due to the significance of some parameters, the impacts of varying working conditions are also investigated. The results of the energetic and exergetic analyses of the integrated system show that the energy and exergy efficiencies are 39.46% and 44.27%, respectively. Furthermore, the system performance increases with the increasing geothermal source temperature and reference temperature while it decreases with the increasing pinch point temperature and turbine inlet pressure. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Geothermal energy; Hydrogen production; Energy; Exergy; Efficiency; EXERGOECONOMIC ANALYSIS; THERMODYNAMIC ANALYSIS; COAL-GASIFICATION; OPTIMIZATION; POLYGENERATION; Chemistry; Electrochemistry; Energy & Fuels